Formed Police Unit dalam Perspektif Hukum Internasional dan Perlindungan Sipil di Wilayah Konflik - Rampengan, Ricky Rifaldi; Moonti, Roy Marthen; Ahmad, Ibrahim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines the role of the Formed Police Unit (FPU) in the perspective of international humanitarian law and international human rights law, particularly in the context of civilian protection in conflict areas. The FPU is an armed police unit deployed in UN peacekeeping missions with a mandate to protect civilians, maintain order, and support post-conflict recovery. Despite its strategic role, the FPU faces legal, operational and socio-cultural challenges. This study uses a normative-juridical approach by analyzing international legal documents, UN operational standards, and academic literature. It is emphasized that the effectiveness of the FPU is highly dependent on human rights-based training, clarity of mandate, logistical readiness, and the ability to build trust with local communities. This article recommends strengthening accountability mechanisms and cross-sector integration in peace missions, so that the FPU is able to carry out its protection mandate substantially and in accordance with applicable international legal principles.